Efficacy of xenogeneic collagen matrix in the treatment of gingival recessions: A systematic review and meta‐analysis. (28th August 2018) - Huang, Jia‐Ping; Liu, Jia‐Mei; Wu, Yan‐Min; Chen, Li‐Li; Ding, Pei‐Hui
Abstract: Objectives: This review aims to evaluate the efficacy of xenogeneic collagen matrix (XCM) for the treatment of single or multiple gingival recessions in terms of clinical parameters and patient‐related outcomes. Materials and Methods: Various electronic databases (The Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, etc.) from 1966 to April 2018 and hand literatures were searched. Quality of the included studies was assessed through the Cochrane Collaboration's Risk of Bias tool. A meta‐analysis was performed to calculate risk ratios and mean differences. Results: Nine randomized controlled trials were included. The results revealed a higher percentage of mean root coverage (MRC) and a greater recession reduction (RecRed) for single recessions for the combination of coronally advanced flap (CAF) with XCM compared to CAF alone ( n = 3; MD = 10.00%; 95%CI [3.56%; 16.43%]; p = 0.002) ( n = 3; MD = 0.35 mm; 95%CI [0.10 mm; 0.60 mm]; p = 0.005). Comparing XCM with connective tissue graft (CTG), no significant differences were detected in MRC or RecRed for single and multiple recessions. Conclusions: The addition of XCM under CAF could improve MRC and RecRed at single tooth recessions. Initial data suggest that XCM shows promising results to improve the clinical efficacy of CAF for multiple recessions. In addition, XCM could be a valid alternative to CTG in terms of MRC and RecRed at both single and multiple recessions. Based on limited evidence, XCM may decrease postoperative morbidity and operation time compared to CTG.